Academic Displacement di Wilayah Konflik: Studi Fenomenologis Mahasiswa Indonesia di Sudan - David Ricardo; Sibawaihi (MAN 4 Kota Pekanbaru, 2026)
The internal conflict in Sudan in 2023 has generated a humanitarian crisis with significant repercussions for higher education, particularly affecting Indonesian students enrolled in Islamic universities. This study aims to examine the phenomenon of academic displacement experienced by Indonesian students in Sudan, encompassing academic, socio-psychological, economic, and administrative impacts, as well as to analyze the resilience strategies developed in response to the conflict. Employing a qualitative approach with a phenomenological method, the research explores students’ subjective experiences through in-depth interviews, contextual observations, and analysis of supporting documents. The findings reveal that armed conflict led to the suspension of learning activities, uncertainty regarding academic status, intense psychological distress, limited access to basic necessities, and administrative barriers that disrupted educational continuity. Despite these challenges, students demonstrated adaptive capacity through the utilization of social networks, community solidarity, family support, and institutional interventions by the Embassy of the Republic of Indonesia. These results underscore that academic displacement constitutes a multidimensional disruption requiring more adaptive and sustainable international education protection policies to safeguard students’ rights and academic trajectories in conflict-affected contexts.